2015
DOI: 10.1159/000439585
|View full text |Cite
|
Sign up to set email alerts
|

The <b><i>COMT</i></b><b><i>p.Val158Met</i></b> Polymorphism and Cognitive Performance in Adult Development, Healthy Aging and Mild Cognitive Impairment

Abstract: Background: The impact of genetic polymorphisms on cognition is assumed to increase with age as losses of brain resources have to be compensated for. We investigate the relation of catechol-O-methyltransferase (COMT)p.Val158Met polymorphism and cognitive capacity in the course of adult development, healthy aging and the development of mild cognitive impairment (MCI) in two birth cohorts of subjects born between 1930 and 1932 or between 1950 and 1952. Methods: Thorough neuropsychological assessment was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…[ 74 ] between MAOA and executive attention and alerting, but the link between rs4680- COMT and the conflict index, based on ANT evaluation, shows that COMT is related to executive control. Several studies have recently associated variants of COMT with cognitive domains such as working memory [ 75 ] or cognitive flexibility [ 76 ]. In addition, this gene has previously been found to be associated with Stroop attentional tasks [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 74 ] between MAOA and executive attention and alerting, but the link between rs4680- COMT and the conflict index, based on ANT evaluation, shows that COMT is related to executive control. Several studies have recently associated variants of COMT with cognitive domains such as working memory [ 75 ] or cognitive flexibility [ 76 ]. In addition, this gene has previously been found to be associated with Stroop attentional tasks [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…COMT has previously been associated with measures of cognition in cognitively normal older adults (Bellander et al, 2015; Starr et al, 2007), in particular episodic memory (Papenberg et al, 2014), working memory (Nagel et al, 2008), and attention (Degen et al, 2016). However, there have been a number of studies in cognitively normal older adults that have reported no significant associations with measures of episodic memory (O’Hara et al, 2006; Stuart et al, 2014), working memory (de Frias et al, 2010), verbal ability (O’Hara et al, 2006), attention or speed of processing (O’Hara et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption to dopamine neurotransmission is associated with brain disease and mental illness. Consequently, allelic variation in the COMT gene has been associated with levels of cognition in cohorts of healthy individuals (Bellander et al, 2015; Degen et al, 2016; Diamond et al, 2004; Dumontheil et al, 2011; Egan et al, 2001; Goldberg et al, 2003; Malhotra et al, 2002; Nagel et al, 2008; Rosa et al, 2004, 2010; Sheldrick et al, 2008; Starr et al, 2007; Stefanis et al, 2005) and schizophrenia patients (Bilder et al, 2002; Egan et al, 2001; Goldberg et al, 2003; Nolan et al, 2004; Rosa et al, 2010), with carriage of COMT Val associated with poorer performance. However, several studies and a meta-analysis (Barnett et al, 2008) investigating healthy (Blanchard et al, 2011; de Frias et al, 2010; Ho et al, 2005; Liu et al, 2014; O’Hara et al, 2006; Papenberg et al, 2014; Potter et al, 2009; Stefanis et al, 2004; Stuart et al, 2014; Wardle et al, 2013) and diseased individuals (e.g., with schizophrenia (Dickerson et al, 2007; Ho et al, 2005; Zilles et al, 2012), depression (Opmeer et al, 2013; Potter et al, 2009; Wang et al, 2014), traumatic brain injury (Willmott et al, 2014), Parkinson’s disease (Hoogland et al, 2010), asymptomatic atherosclerosis (Bolton et al, 2010)) have reported no association between COMT genotype and cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Met allele has been associated with lower enzyme activity and elevated dopamine levels. Conversely, the Val allele has been associated with higher enzyme activity and reduced dopamine levels [15,16]. Therefore, COMT can modulate aspects of cognition, emotion and behavior [15,17].…”
Section: Introductionmentioning
confidence: 99%